Weed control in major tropical root and tuber crops: review - Moody, K.; Ezumah, H.C. (Informa UK Limited, 1974)
The present status of weed control in the major tropical root and tuber crops is reviewed. The importance of early weeding is emphasised and summaries of the results obtained with herbicides are given.